Inside Threat : A Thriller - Quirk, Matthew (New York : William Morrow, 2024)
An attack on the White House sends the President and his top aides to take shelter in a top secret government facility buried deep underground--but they soon discover the threat is locked inside with them.
Keywords: White House (Washington, D.C.) -- Fiction; Secret service -- United States -- Fiction; Presidents -- United States -- Fiction; Conspiracies -- Fiction; Police corruption -- Fiction; Spy fiction; Political fiction; Thrillers (Fiction)